Propolis: Effect of different concentrations, extracts and intake period on seric biochemical variables - Mani, F.; Damasceno, HCR; Novelli, ELB; Martins, EAM; Sforcin, J. M. (Elsevier B.V., 2006)
Propolis is a resinous substance produced by honeybees that possesses many biological activities, such as antitumor, antioxidant, antimicrobial, anti-inflammatory, and immunomodulatory, among others. The purpose of the present study was to investigate the biochemical profile of propolis-treated rats to observe whether propolis might lead to side effects after administration. Three different treatments were analyzed: (1) rats were treated with different concentrations of propolis (1, 3 and 6 mg/kg/day) during 30 days; (2) rats were treated with I mg/kg/day of ethanolic or water extracts of propolis (EEP, WEP) during 30 days; (3) rats were treated with I mg/kg/day of ethanolic extract of propolis during 90 and 150 days. Our results demonstrated no alterations in the seric levels of cholesterol, HDL-cholesterol, total lipids, triglycerides and in the specific activity of aminotransferases (AST) and lactic dehydrogenase (LDH) of propolis-treated groups when compared to controls. on the basis of our findings, since propolis does not induce any significant change in seric parameters, it is claimed that long-term administration of propolis might not have any cardiac injury. (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: propolis; extracts; biochemical variables; cardiotoxicity